The presentation and outcomes of mucosal melanoma in 695 patients. Issue 1 (14th September 2016) - Konuthula, Neeraja; Khan, Mohemmed N.; Parasher, Arjun; Del Signore, Anthony; Genden, Eric M.; Govindaraj, Satish; Iloreta, Alfred M.
Abstract : Background: Most data on sinonasal mucosal melanoma come from small institutional studies, and therefore optimal treatment methods are not well understood. The purpose of this study was to analyze the association between treatment and survival in sinonasal mucosal melanoma. Methods: Six hundred ninety–five patients diagnosed with sinonasal mucosal melanoma between 2004 and 2010 were identified from the National Cancer Data Base. Treatment modalities and overall survival rates were determined. Results: The 5–year overall survival was 21.7%, with a mean survival of 38.4 ± 1.7 months. The majority of patients were treated with surgery alone (31.5%) or surgery with adjuvant radiotherapy (41.4%). There was no statistical difference between survival with surgery alone and surgery with adjuvant radiation therapy (25.1% vs 25.1%, p = 0.93). Between the surgery and surgery–with–adjuvant–therapy groups, there was no difference in the number of patients with positive margins ( p = 0.54), regional lymph node metastases at diagnosis ( p = 0.55), morbidity scores ( p = 0.58), insurance status ( p = 0.13), age > 60 years ( p = 0.24), or treatment at academic centers ( p = 0.12). Conclusions: Based on this large review of patients with sinonasal mucosal melanoma, adjuvant radiation therapy may not provide a survival benefit as patients tended to do poorly regardless of adjuvant radiation status.